PERAN RASIO LIKUIDITAS, PROFITABILITAS, AKTIVITAS UKURAN PERUSAHAAN DAN KEBIJAKAN HUTANG TERHADAP HARGA SAHAM - Ni Made Mia Dwilestari; Ni Luh Gde Novitasari; Widhiastuti, Ni Luh Putu (Universitas Dian Nuswantoro, 2025)
This study aims to determine the effect of ratio of liquidity, ratio of profitability, rasio of activity, company size and debt policy on stock price of mining companies in the Indonesian Stock Exchange (Bursa Efek Indonesia) on a period of 2020-2022. Independent variables include ratio of liquidity, ratio of profitability, rasio of activity, company size and debt policy. The sample of this research is 25 companies choosed by using purposive sampling technique. The type of data used is secondary data. The analysis technique used in this study is multiple linier regression. The results showed that The results of this study indicate that the variable company size have apositive effect on stock prices. While the variables ratio of liquidity, ratio of profitability, rasio of activity, and debt policy have no effect on stock prices.